2006
DOI: 10.1111/j.1532-849x.2006.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Prosthodontics as a Specialty Private Practice: Net Income of Private Practitioners

Abstract: Average net earnings are often used to examine the current economic health of a profession. The average net earnings of prosthodontists in private practice exceed the average net income reported by the American Dental Association for all dentists and all general practitioners and they are competitive with earnings among all specialty groups. This evaluation of the net earnings of prosthodontists shows that prosthodontics offers a competitive career opportunity for the general dentist with a personal desire to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…15 The general decline in enrollment in US prosthodontic residency programs (−2.9% per year), coupled with an expectation of doubling the net income in private practice, may keep the number of specialists who chose an academic career path low for the immediate future. 16,17 Board certification is a lengthy but personally gratifying professional experience, which may not offer any financial gain for the private practitioner. The majority of prosthodontic board diplomates are in the military, which encourages pursuit of and compensates for specialty board certification.…”
Section: Discussionmentioning
confidence: 99%
“…15 The general decline in enrollment in US prosthodontic residency programs (−2.9% per year), coupled with an expectation of doubling the net income in private practice, may keep the number of specialists who chose an academic career path low for the immediate future. 16,17 Board certification is a lengthy but personally gratifying professional experience, which may not offer any financial gain for the private practitioner. The majority of prosthodontic board diplomates are in the military, which encourages pursuit of and compensates for specialty board certification.…”
Section: Discussionmentioning
confidence: 99%
“…These sources include the 2002 3 and 2005 4 Survey of Prosthodontists conducted by the American College of Prosthodontists (ACP). The purpose of the surveys was to gather appropriate information to assist the ACP in formulating a program encouraging dentists to consider a career in the profession of prosthodontics.…”
Section: Methodsmentioning
confidence: 99%
“…Our finding was in agreement with previous data. Nash and Pfeifer 18,19 showed that the average earnings for prosthodontists in private practices were estimated to be $213,742 ± $167,488; male prosthodontists earned 30% more than female prosthodontists, and the mean earnings grew as prosthodontists gained more experience.…”
Section: Future Trendsmentioning
confidence: 97%
“…[8][9][10][11][12][13][14] Studies related to AEP have been based on surveys of program directors, deans, and practicing prosthodontists. [15][16][17][18][19] A recent study for the first time surveyed AEP residents on which factors might influence residents in choosing prosthodontics as their specialty. 20 The study reported that residents considered the complexities and challenges of treatment planning and execution of prosthodontic treatment to be the most important factors in deciding to specialize in prosthodontics.…”
mentioning
confidence: 99%